Gender, power, sexuality and suffering bodies in the Book of Esther : reading the characters of Esther and Vashti for the purpose of social transformation - Nadar, Sarojini (Old Testament essays, 2002)
Suffering bodies are indeed high on the agenda in the Book of Esther. As Timothy Beal (1997:2) points out, the losers in the story end up 'dethroned, banished, disenfranchised, dead in a pile, or impaled on a stake'. The suffering bodies are intricately tied up with issues of gender, power, sexuality, ethnicity and identity. By deconstructing oppressive gender and ethnic assumptions in my literary reading of the two major female characters I show how the text of Esther can be read as an empowering and liberating text for women in suffering contexts in South Africa. The majority of South African women view the Bible as a crutch on which to lean in difficult times. Yet the issues that preoccupy scholars about Biblical narratives are also the issues that affect these 'ordinary' women. Texts like Esther can impact women living under the triple oppression of race, class and gender in a very direct and pervasive manner. A reading such as the one undertaken in this paper is meaningful not only to the academic, but also to the ordinary (woman) reader. My analysis comprises literary, postmodernist and South African womanist methodologies.